2000
DOI: 10.1094/pdis.2000.84.12.1282
|View full text |Cite
|
Sign up to set email alerts
|

Evidence thatXylella fastidiosaCan Cause Leaf Scorch Disease of Pecan

Abstract: The disease known as pecan fungal leaf scorch has been reported to be either caused by or associated with several fungi since it was first recognized in 1972. Data are presented that indicate the disease is initiated by the fastidious xylem-limited bacterium Xylella fastidiosa. X. fastidiosa was found consistently associated with fungal leaf scorch disease of pecan (Carya illinoinensis) in commercial orchards in Louisiana. It was generally not detected in symptomless trees. The disease was reproduced by inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…It grows optimally from 26 to 28°C and is described as ''nutritionally fastidious,'' requiring specialized media for growth in the laboratory. Sanderlin and Heyderich-Alger (2000) reported that X. fastidiosa causes leaf scorch in pecan, which has become known as Pecan Bacterial Leaf Scorch (PBLS). A disease screen of commercial cultivars for susceptibility to PBLS (Sanderlin, 2005) reported variable expression of leaf scorch, with all susceptible to infection and symptom development.…”
Section: Threats Of Genetic Erosion In Situmentioning
confidence: 99%
“…It grows optimally from 26 to 28°C and is described as ''nutritionally fastidious,'' requiring specialized media for growth in the laboratory. Sanderlin and Heyderich-Alger (2000) reported that X. fastidiosa causes leaf scorch in pecan, which has become known as Pecan Bacterial Leaf Scorch (PBLS). A disease screen of commercial cultivars for susceptibility to PBLS (Sanderlin, 2005) reported variable expression of leaf scorch, with all susceptible to infection and symptom development.…”
Section: Threats Of Genetic Erosion In Situmentioning
confidence: 99%
“…These include PD in grapevines (Davis et al ., 1981; Hopkins and Purcell, 2002), leaf scorches in pecan (Sanderlin and Heyderich-Alger, 2000; Sanderlin and Melanson, 2006), pear (Leu and Su, 1993), plum (Raju et al ., 1983), almond (Mircetich et al ., 1976), mulberry (Kostka et al ., 1986), elm, sycamore, oak (Hearon et al ., 1980), maple (Sherald et al ., 1987), coffee (de Lima et al ., 1998), oleander and olives (Saponari et al ., 2013), as well as alfalfa dwarf (Goheen et al ., 1979), phony peach disease (Wells et al ., 1981), periwinkle wilt (McCoy et al ., 1978), and citrus variegated chlorosis (Chang et al ., 1993; Hartung et al ., 1994). Strains of X. fastidiosa have a wide host range in the native flora, where they exist without inducing symptoms of disease, and they are transmitted by common sharpshooter insects (Freitag, 1951; Freitag and Frazier, 1954).…”
Section: The Plant Pathogen Xylella Fastidiosamentioning
confidence: 99%
“…The previously mentioned symptoms were inconsistent with any previously reported blueberry disease. It was noticed, however, that the symptoms were similar to diseases caused by X. fastidiosa in other plants in south Georgia such as plum leaf scald (Raju et al, 1982;Wells et al, 1987) or pecan bacterial leaf scorch (Sanderlin and Heyderick-Alger, 2000). This observation prompted the initiation of testing to determine whether X. fastidiosa could cause these symptoms, and subsequent death, of blueberry plants.…”
mentioning
confidence: 99%